2018
DOI: 10.1007/s11284-018-1560-x
|View full text |Cite
|
Sign up to set email alerts
|

Inducing Ni sensitivity in the Ni hyperaccumulator plant Alyssum inflatum Nyárády (Brassicaceae) by transforming with CAX1, a vacuolar membrane calcium transporter

Abstract: The importance of calcium in nickel tolerance was studied in the nickel hyperaccumulator plant Alyssum inflatum by gene transformation of CAX1, a vacuolar membrane transporter that reduces cytosolic calcium. CAX1 from Arabidopsis thaliana with a CaMV35S promoter accompanying a kanamycin resistance gene was transferred into A. inflatum using Agrobacterium tumefaciens. Transformed calli were sub‐cultured three times on kanamycin‐rich media and transformation was confirmed by PCR using a specific primer for CAX1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…Zinc was the most significant antagonistic factor to Cd. The antagonistic interaction of the translocation factors of Zn and Cd is predictable, because Cd can enter the plants cells by competing for transporter and channel protein [34,35].Thus, Cd uptake is related to cation absorption, and Cd accumulation will be reduced when abundant divalent cations are present. The tubers demonstrated the highest Zn accumulation at a Cd dose of 1.00 mg/kg (II) in the first year (T 1 ) and at a Cd dose of 0.37 mg/kg (I) in the second year (T 2 ), except T 2-7 .…”
Section: Discussionmentioning
confidence: 99%
“…Zinc was the most significant antagonistic factor to Cd. The antagonistic interaction of the translocation factors of Zn and Cd is predictable, because Cd can enter the plants cells by competing for transporter and channel protein [34,35].Thus, Cd uptake is related to cation absorption, and Cd accumulation will be reduced when abundant divalent cations are present. The tubers demonstrated the highest Zn accumulation at a Cd dose of 1.00 mg/kg (II) in the first year (T 1 ) and at a Cd dose of 0.37 mg/kg (I) in the second year (T 2 ), except T 2-7 .…”
Section: Discussionmentioning
confidence: 99%
“…The first article reports on an experimental study of the physiology of the Ni-hyperaccumulator Leptoplax emarginata (Brassicaceae), and the results show that the highest Ni concentrations are in the actively transpiring young, thin leaves with the greatest stomatal densities (Bartoli et al 2018). In another study (Ghasemi et al 2018) investigating the role of the CAX1 Ca 2+ vacuole transporter in the Ni-hyperaccumulator Alyssum inflatum (Brassicaceae), it is concluded that high cytosolic Ca 2+ is an important parameter that results in Ni tolerance. An investigation of the mechanisms involved in Mn hyperaccumulation by Phytolacca americana suggests that this trait may be a side effect of rhizosphere acidification as a phosphorus-acquisition mechanism, rather than an adaptation to high soil Mn per se (DeGroote et al 2018).…”
Section: Ecophysiology Of Metallophytes and Metal Hyperaccumulationmentioning
confidence: 99%
“…The same authors emphasized the importance of Calcium for normal plant physiological functioning and survival. In western Iran, the survival rate of a serpentine-endemic Alyssum inflatum was reduced at Ca: Mg = 0.4 ratio and maximum at Ca: Mg = 2 (Ghasemi et al, 2018). However, the authors further noted that at a higher Ca: Mg ratio (i.e., > 20) (Wahsha et al, 2012).…”
Section: Discussionmentioning
confidence: 95%